Resilience in deaf children adaptation through emerging adulthood - Pierc (Springer, 2011)
(Publisher-supplied data) Historically, the diagnosis of deafness in a child has been closely associated with profound disability, including such typical outcomes as unmet potential and a life of isolation. A major shift away from this negative view has led to improved prospects for deaf children. Resilience in Deaf Children emphasizes not only the capability of deaf individuals to withstand adversity, but also their positive adaptation through interactions with parents, peers, school, and community. In this engaging volume, leading researchers and professionals pay particular attention to such issues as attachment, self-concept, and social competence, which are crucial to the development of all young people. In addition, the volume offers strategies for family members, professionals, and others for promoting the well-being of deaf children and youth. Coverage includes: Attachment formation among deaf infants and their primary caregivers.Deaf parents as sources of positive development and resilience for deaf infants.Enhancing resilience to mental health disorders in deaf school children.Strength-based guidelines for improving the developmental environments of deaf children and youth.Community cultural wealth and deaf adolescents resilience.Self-efficacy in the management of anticipated work-family conflict as a resilience factor among young deaf adults.Resilience in Deaf Children is essential reading for researchers, clinicians, and graduate students in clinical child, school, and developmental psychology as well as for allied researchers and professionals in such disciplines as school counseling, occupational therapy, a